Viral Bacterial Artificial Chromosomes: Generation, Mutagenesis, and Removal of Mini-F Sequences. (23rd February 2012) - Tischer, B. Karsten; Kaufer, Benedikt B.
Abstract : Maintenance and manipulation of large DNA and RNA virus genomes had presented an obstacle for virological research. BAC vectors provided a solution to both problems as they can harbor large DNA sequences and can efficiently be modified using well-established mutagenesis techniques in Escherichia coli . Numerous DNA virus genomes of herpesvirus and pox virus were cloned into mini-F vectors. In addition, several reverse genetic systems for RNA viruses such as members of Coronaviridae and Flaviviridae could be established based on BAC constructs. Transfection into susceptible eukaryotic cells of virus DNA cloned as a BAC allows reconstitution of recombinant viruses. In this paper, we provide an overview on the strategies that can be used for the generation of virus BAC vectors and also on systems that are currently available for various virus species. Furthermore, we address common mutagenesis techniques that allow modification of BACs from single-nucleotide substitutions to deletion of viral genes or insertion of foreign sequences. Finally, we review the reconstitution of viruses from BAC vectors and the removal of the bacterial sequences from the virus genome during this process.